Effect of Ketapang Leaves (Terminalia catappa L.) Extract in Drinking Water on Performance, Hematological Indices and Immune Response of Kampong-Crossbreed Chicken During Starter Period - Marifah, Binti; Suprijatna, Edjeng; Mahfudz, Luthfi Djauhari; Muryani, Rina (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
This study was aims to evaluate the potential of ketapang leaves extract (Terminalia catappa L.) as a feed additive on growth performance, haematological profile and immune respone in starter period of kampong-crossbreed chickens. Observations were made in vitro and in vivo. In vitro observations were carried out on the anti-bacterial activity, anti-fungal activity and antioxidant activity. In vivo observations were carried out on the growth performance, haematological profile and immunity response with the antigen test against NDV in starter period (4 weeks old). Two types of liquid extract are used, namely the liquid extract of fresh ketapang leaves and dry ketapang leaves. Ketapang leaves liquid extract is given in a mixture of drinking water with a concentration of 1, 2, 3 and 4% (ml / 100ml). The results showed that in vitro extracts of fresh and dry ketapang leaves had an effect on bacterial and fungal activity and antioxidant activity. In vivo observations showed no effect on performance, but had an effect on haematological profiles and immune respone. Dried ketapang leaf extract showed a better effect on haematology and immune respone.